(untitled) (Perner’s Contacts, 2012)
The aim of the paper is to explain important factors that need to be taken into consideration when constructing load distribution diagrams of railway wagon. Technical characteristics as well as UIC Loading guidelines requirements have to be considered. Load distribution diagram is a visual presentation of the area where the total cargo centre of gravity of certain mass have to be located. This can be done without calculations of axle/boogie loads and consideration of boogie loads inequality..